Renal venous sampling assisted the diagnosis of juxtaglomerular cell tumor: a case report and literature review - Yan, Di-en; He, Hong-bing; Guo, Jian-ping; Wang, Yu-lan; Peng, Dan-ping; Zheng, Huan-huan; Zhou, Xiao-zi; Fu, Jin-xiang; Wang, Mei-li; Luo, Xian; Shen, Yun-feng (Frontiers in Oncology, 2024)
Juxtaglomerular cell tumor (JCT) is an endocrine tumor marked by elevated renin levels and high blood pressure. This case report presents the clinical findings of a 47-year-old woman with a history of recurrent hypokalemia, headaches, hypertension, and increased plasma renin activity (PRA). Dynamic enhanced Magnetic Resonance Imaging (MRI) revealed a small nodule on the upper part of the right kidney. Selective renal venous sampling indicated higher PRA only in the right upper pole renal vein. The patient underwent surgical removal of the right kidney mass, and pathology confirmed the diagnosis of JCT. This case underscores the importance of conducting selective renal venous sampling for accurate JCT diagnosis.